INTERSTATE COLLECTIVE SECURITY: ITS DEVELOPMENT AND DECLNE - Van der Waag, Ian (Scientia Militaria - South African Journal of Military Studies, 2012)
The idea of collective security and its later development, the regional collective defence alliance, is particularly interesting in the light of our contemporary situation. Not only because the utter failure of the first has led to the rise of the second, but because the defence alliance implies a reverting to the old balance of power, which was rejected during the First World War in favour of the collective security system, thus now forming a complete cycle.